2012
DOI: 10.1089/end.2011.0584
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Direct Cost Analysis of Pediatric Urologic Robot-Assisted Laparoscopic Surgery Versus Open Surgery: Could Robot-Assisted Surgery Be Less Expensive?

Abstract: Direct costs for robot-assisted surgery were significantly lower than equivalent open surgery. Factors reducing robot-assisted surgery costs included: A consistent and trained robotic surgery team, an extensive history of performing urologic robotic surgery, selection of patients for robotic surgery who otherwise would have had longer hospital stays after open surgery, and selection of procedures without a laparoscopic alternative. The high indirect costs of robot purchase and maintenance remain major factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 13 publications
2
41
0
1
Order By: Relevance
“…Cystoscopy with retrograde stent placement was performed in all of the pure laparoscopic cases. For the 23 robotic cases stent placement via antegrade (10) or retrograde (13) approach was based on attending preference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystoscopy with retrograde stent placement was performed in all of the pure laparoscopic cases. For the 23 robotic cases stent placement via antegrade (10) or retrograde (13) approach was based on attending preference.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Prior cost analyses comparing robotic and laparoscopic pyeloplasties have concluded that the laparoscopic approach is significantly less expensive, although analyses were based on an adult population and differed in their allocation of indirect costs. 8,9 In the pediatric urology literature robotic surgery has been shown to be less expensive compared to open surgery, 10 although there has been no comparison of the cost of pediatric laparoscopic and robotic pyeloplasties. Due to variation among institutions and the need to standardize results among studies, we retrospectively identified a representative series of robotic and laparoscopic pyeloplasties performed at our institution, and performed a cost analysis.…”
mentioning
confidence: 99%
“…For the same surgical procedure, robot-assisted surgery appeared significantly less expensive than open surgery (11.9% lower than open surgery; $9,550.13 vs $10,834.70; p = 0.03) [50] and than laparoscopy ($16,595 vs $17,384; p b 0.46 and $12,929 vs $17,384; p = 0.0001) when stents were placed in an antegrade fashion [51].…”
Section: Analysis and Findings Of Ees In Pediatric Urologymentioning
confidence: 97%
“…Growing evidence suggests that the cost of robotic devices can deter hospitals from introducing new technologies into clinical practice [33]- [35]. For this reason the system should not require expensive special tools but should operate with a standard coaxial needle (Somatex, Teltow, Germany).…”
Section: B System Requirementsmentioning
confidence: 99%